Efektivitas Pemanfaatan Dana Desa Dalam Menunjang Perekonomian Masyarakat Di Kecamatan Gunung Tuleh (Studi Kasus Nagari Rabijonggor): (Studi Kasus Nagari Rabijonggor) - Anggian Anggian; Fajar Budiman; Fawza Rahmat (Journal of Management and Creative Business, 2023)
Facts on the ground, when channeling funds there are requirements that are not well understood so employee performance is slow in the distribution process and human resources are still not good. The formulation of the problem in this research is the effectiveness of the utilization of Village funds in supporting the economy of the community in Gunung Tuleh Sub-District (case study of Nagari Rabi Jonggor). Jonggor). The theory used in this study is a theory related to effectiveness, village funds, the economy, and nagari. Effectiveness is a key element to achieve the goals or objectives that have been determined in every organization, activity or program. It is called effective if the goal or target is achieved as it has been found. The type of research used is descriptive qualitative research. Sources of data used in this research are primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis used in this research is data reduction, data presentation and conclusion. The results of the study show effectiveness at the level of achieving goals, a business can be said to be effective if the effort is achieved ideally, effectiveness can be said with relatively certain measures of the use of village funds that have been realized properly such as the work program of Nagari Rabi Jonggor in the fields of health, economy, and the social field. The effectiveness of the use of village funds can be said to be effective because seen from the priorities for the use of village funds it is in accordance with the Permendes (Regulation of the village minister. development of underdeveloped areas, and transmigration